Come un gatto in tangenziale - Milani, Riccardo 1958-; Cortellesi, Paola 1973-; Albanese, Antonio 1964- (2018)
The story of an encounter between a bourgeois man and a poor woman when their teenage children get engaged
Videodisc of the motion picture originally produced in 2017
Includes backstage extras
Keywords: Social classes / Italy / Drama; Social classes; Italy; Comedy films; Drama; Feature films; Film; DVD-Video